2020
DOI: 10.1590/1983-21252020v33n124rc
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Intervals in the Production of Ornamental Pineapple in Pots1

Abstract: Information on irrigation management is essential in a production system for the commercial cultivation of ornamental pineapple in pots. As such, this work evaluated the effects of irrigation interval on the growth and production of the crop in pots. The experiment was carried out from 16/07/2015 to 21/05/2016 in a greenhouse located in Fortaleza, in the state of Ceará, Brazil. The experimental design was completely randomised, with five treatments, four replications and four plants per plot. The treatments co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…opened flowers and flower diameter than irrigating daily or every 2 days. Do Bomfim et al (2020) found that, for Ananas comosus var. Erectifolius, the irrigation interval at 2 days highly improved the plant height, No.…”
Section: Effect Of Irrigation Interval Media and Their Interactions O...mentioning
confidence: 99%
“…opened flowers and flower diameter than irrigating daily or every 2 days. Do Bomfim et al (2020) found that, for Ananas comosus var. Erectifolius, the irrigation interval at 2 days highly improved the plant height, No.…”
Section: Effect Of Irrigation Interval Media and Their Interactions O...mentioning
confidence: 99%
“…This true was documented by Abdel-Moneim et al (2018) on Euphorbia milii var. longifolia, El-Leithy et al (2018) on rosemary, Akhtar (2019) on Calendula officinalis and Dianthus barbatus, Do Bomfim et al (2020) on ornamental pineapple and Scagel and Bryla (2022) on Rhododendron cvs. Gibraltar, PJM and Catawbiense Album.…”
Section: Anothermentioning
confidence: 99%